Antibacterial Effect of Cinnamon and Citronella Oils Combination Against Acne-Related Bacteria - Sri Mulyaningsih; Arya Guna Ramadhan; Widyasari Putranti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Acne vulgaris is a dermatological disease whose pathogenesis is due to high sebum secretion, hyperkeratinization, hormonal changes, or bacterial infections. Staphylococcus epidermidis and Staphylococcus aureus are bacteria that can induce inflammation in acne. Cinnamomum burmannii and Cymbopogon nardus essential oils have been reported to have antibacterial activity against S. epidermidis and S. aureus. This study aimed to obtain the type of interaction of a combination of C. burmannii and C. nardus oils in inhibiting bacteria associated with acne. Essential oil components were identified using gas chromatography-mass spectrometry (GCMS). Optimize the combination of C. burmannii and C. nardus oils using the checkerboard method. Furthermore, the Fractional Inhibitory Concentration Index (FICI) value is calculated to determine the effect of a combination that is synergistic, additive, not different or antagonistic. The main components of C. burmannii oil identified are cinnamaldehyde, eucalyptol, cinnamyl acetate, α-limonene, and α-terpineol. While C. nardus oil contains the five largest components: geraniol, citronellal, citronellol, citral, and geranyl acetate. Cinnamomum burmannii oil yielded 0.28%, with a refractive index of 1.5237. Meanwhile, the yield of C. nardus oil was 0.26%, with a refractive index of 1.4667. The combination of both oils yielded a FICI value of 1.5. The conclusion of this study shows that the combination of the two essential oils produces an indifferent effect against both S. epidermidis and S. aureus.